안와벽 골절 면적과 이탈된 안와내 조직의 부피에 따른 안구함몰 정도 - 장학선(Hak-Sun Jang); 임대호(Dae-Ho Leem); 백진아(Jin-A Baek); 신효근(Hyo-Keun Shin); 고승오(Seung-O Ko) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2011)
Introduction: The enlargement and deformation of the orbit give rise to a visible enophthalmos. As a consequence, a disturbance of eye motility together with double images is likely to occur. This study examined the degree of enophthalmos according to the extent of orbital wall fracture and volume of herniated orbital tissue in blowout fractures of the medial and inferior orbital wall. Materials and Methods: This study was performed on patients diagnosed with medial and inferior orbital wall fractures at the Department of Oral and maxillofacial surgery, Chonbuk National University Hospital from 2007 to 2009. The patients' age, gender, etiology of fracture and degree of enophthalmos were investigated. The changes in the degree of enophthalomos, diplopia and ocular motility restriction after operation were examined. Results: The degree of enophthalomos increased with increasing extent of orbital wall fracture and volume of herniated orbital tissue. Conclusion: Whether to perform the operation is decided after measuring the extent of the orbital wall fracture and volume of herniated orbital tissue using computed tomography (CT), time for the decision of operation can be shortened. This can cause a decrease in the complications of orbital wall fractures. KCI Citation Count: 1